ICMS importação e a Emenda Constitucional nº 33/2001: uma hermenêutica constitucional dos fatos - Cardoso, Enio Fernando Gomes (2010)
This project is intended to demonstrate the major changes undergone by ICMS with the advent of the constitutional amendment nº 33/2001. By assuming an important role in Brazilian constitutional scenario, we tried to emphasize throughout the paper a thorough study of the constitutional archetype of that tax, revealing their innovations and changes over time, and of course other aspects of vital importance for hermeneutical, as the analysis of the impact hypothesis and observation to constitutional principles and rules. It is from these revelations that we reach the final conclusion to be unconstitutional the content of the constitutional amendment nº 33/2001 regarding the proposed new impact hypothesis for the ICMS, not only because it violates principles of Brazilian Constitutional Law, most above all by mitigating rights of brazilian taxpayer